"Aur Market Place" - Activator and Interaction Space to Support and Living Up Tourism of Kelurahan Aur. Issue 1 (April 2020) - Maharani, A; Kamajaya, P
Abstract: Istana Maimun (Maimoon Palace), located in Kelurahan Aur is one of the historical heritage Palaces during Deli Sultanate era that still stands beautifully and becoming an iconic Landmarks of Medan – Sumatera Utara, Indonesia. This Palace has a lot of historical value in branding identity also an image of Medan regarding the Glory of Deli Sultanate in the past and has a strategic location in the side of Deli River. The potential river which should be one of attraction becomes a place for waste by locals and causing problems that its existence is being covered. After a site visit and collecting data from different sources, authors think that Aur region has potential to the development of cultural, artistic, and historical tourism. However, this area still shortcoming of tourism aspects, such as commercial facilities, activities, attractions, access, and accommodations that can make visitors feel welcomed and want to spend their time enjoying the atmosphere. Therefore, authors trying to introduced more of mixed facilities that can be called as "Aur Market Place" which hopefully can support the optimization of Istana Maimun and surround its area in continuous ways, where this public space can be activator of another development by government towards Aur region and becoming magnets for all ages which can lead interactions between locals and tourist in one place.